Secondary-Sphere Effects in Molecular Electrocatalytic CO2 Reduction - Nichols, Asa W.; Machan, Charles W. (Frontiers in Chemistry, 2019)
The generation of fuels and value-added chemicals from carbon dioxide (CO2) using electrocatalysis is a promising approach to the eventual large-scale utilization of intermittent renewable energy sources. To mediate kinetically and thermodynamically challenging transformations of CO2, early reports of molecular catalysts focused primarily on precious metal centers. However, through careful ligand design, earth-abundant first-row transition metals have also demonstrated activity and selectivity for electrocatalytic CO2 reduction. A particularly effective and promising approach for the enhancement of the reaction rates and efficiencies of molecular electrocatalysts for CO2 reduction is the modulation of the secondary coordination sphere of the active site. In practice this has been achieved through the mimicry of enzyme structures: incorporating pendent Brønsted acid/base sites, charged residues, sterically hindered environments, and bimetallic active sites have all proved to be valid strategies for iterative optimization. Herein, the development of secondary sphere strategies to facilitate rapid and selective CO2 reduction is reviewed with an in-depth examination of the classic [Fe(tetraphenylporphyrin)]+, [Ni(cyclam)]2+, Mn(bpy)(CO)3X, and Re(bpy)(CO)3X (X = solvent or halide) systems, including relevant highlights from other recently developed ligand platforms.